Surrender - Loriga, Ray, 1967- (Houghton Mifflin Harcourt, 2020)
"From award-winning Spanish author Ray Loriga comes a dystopian novel about authority, manipulation, and the disappearance of privacy that "calls to mind The Handmaid's Tale by Margaret Atwood [and] Blindness by Jose Saramago" (Alfaguara Prize Winner Citation)"--